The Internet for dummies quick reference - Levine, John R (IDG Books Worldwide, 1994)
A comprehensive source of information about the world's largest and most complex network of networks: the Internet. This easy-to-read reference is filled with plain English explanations of just what the Internet is, what you can get from it, and--most importantly--how to get it. Cross-referenced to The Internet for Dummies.